2009
DOI: 10.1071/mf08358
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of the Riparian Mapping Tool to identify priority rehabilitation areas for nitrogen removal in the Tully - Murray basin, Queensland, Australia

Abstract: Abstract. One feature of riparian zones is their ability to significantly reduce the nitrogen loads entering streams by removing nitrate from the groundwater. A novel GIS model was used to prioritise riparian rehabilitation in catchments. It is proposed that high-priority areas are those with a high potential for riparian denitrification and have nearby land uses that generate high nitrogen loads. For this purpose, we defined the Rehabilitation Index, which is the product of two other indices, the Nitrate Remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This too can cause large spatial variations in groundwater nitrogen concentrations. The benefits of such riparian zones have already been shown in studies in this region (McKergow et al , 2004a,b) and have led to the identification of priority revegetation areas on this floodplain (Hunter et al , 2006; Rassam and Pagendam, 2009) and extensive riparian replanting has been undertaken by the local council. However, our chemical balance of Kyambul lagoon will include any water quality improvement provided by the surrounding riparian vegetation, but without any knowledge of the groundwater quality entering this zone we cannot quantify its effect separately.…”
Section: Resultsmentioning
confidence: 93%
“…This too can cause large spatial variations in groundwater nitrogen concentrations. The benefits of such riparian zones have already been shown in studies in this region (McKergow et al , 2004a,b) and have led to the identification of priority revegetation areas on this floodplain (Hunter et al , 2006; Rassam and Pagendam, 2009) and extensive riparian replanting has been undertaken by the local council. However, our chemical balance of Kyambul lagoon will include any water quality improvement provided by the surrounding riparian vegetation, but without any knowledge of the groundwater quality entering this zone we cannot quantify its effect separately.…”
Section: Resultsmentioning
confidence: 93%
“…Whilst riparian zones are known to reduce DIN through the process of denitrification, a range of conditions are required for this to occur. These include appropriate floodplain hydrology, high levels of organic carbon through the soil profile, anaerobic conditions, and appropriate residence time (Rassam and Pagendam, ). It is possible that the reason we found that riparian vegetation did not reduce the concentration of DIN as some might have expected was because the conditions for denitrification to occur were not met.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of riparian vegetation was a key directive of the Tully WQIP for its potential to deliver supporting and regulating water quality ecosystem services (Kroon et al, 2009). In addition to shade for temperature and aquatic weed regulation, riparian vegetation may also filter groundwater nitrate, trap sediments, and reduce erosion ( Rassam and Pagendam, 2009;Pert et al, 2010). To locate target areas for restoration that would provide the best return on investment, riparian ecosystem services in the Tully Murray floodplain have been mapped (Pert et al, 2010), including riparian areas with high denitrification ability near agricultural land with elevated nutrient loads (Rassam and Pagendam, 2009).…”
Section: Restoration Case Study 3: Riparian Habitat Loss and Reduced mentioning
confidence: 99%
“…This interest extends beyond water quality benefits, with potential to provide an economic benefit to landholders through public/private market schemes investing in restoration "green" projects . Additional water quality co-benefits could be gained by planting riparian buffers around constructed wetlands, enhancing filtration capacity of the low-lying land through denitrification by riparian vegetation (Rassam and Pagendam, 2009).…”
Section: Restoration Case Study 3: Riparian Habitat Loss and Reduced mentioning
confidence: 99%